أثر القرآن الكريم في أدب النصارى من أدباء المهجر Impact of the Quran in the literature of the Christians of the Diaspora writers - Walid F.T Shehada; Tengku Ghani Tengku Jusoh; Maheram Ahmad (Universiti Kebangsaan Malaysia, 2012)
Arabic literature influenced in the Holy Quran after coming to the prophet Muhammad, peace be upon him, then poets and writers took from it, through the ages, term, meanings, images, and compositions. So, Renaissance literature calls for good values and Islamic authenticity. The study comes to show the impact of the Holy Quran as produced by the Christian of literary diaspora who have been affected by movements of renewal world –European and American – having emigrated to America and settled primarily in the land of the west and print out lifestyle there, and integrated into western society and learned a lot of languages, making them strangers Arabs for Arabic, however, the Holy Quran with its meaning and style colored what is going on in their minds and hearts. The study focuses on three writers as flags of diaspora literature, and that by reading what they wrote on both prose and poem in order to identify the impact of the Holy Quran upon their literature.